2020
DOI: 10.2340/16501977-2652
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based rehabilitation to reduce post-stroke fatigue is not effective: A randomized controlled trial

Abstract: We have performed the first randomized controlled study on a nature-based intervention for patients with post stroke fatigue. Nature Based Interventions are performed in outdoor environment especially suitable/ adopted for supporting treatment and rehabilitation programs. A total of 101 patients were randomized into a two-armed study: 1) treatment as usual, and 2) nature-based intervention. There were no statistical differences confirmed between the treatments, which may be partly explained by several methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Twelve studies reported depression as an outcome, of which seven used the Beck Depression Inventory (Bang et al, 2016, 2017; Cho et al, 2008; Chun et al, 2017; Han et al, 2016), two used Zung's Depression Scale (Choi & Ha, 2014; You et al, 2014), two used Hospital Anxiety and Depression Scale (Kim et al, 2015; Pálsdóttir et al, 2020) and one used Geriatric Depression Scale—Korea Version (Lim et al, 2014). Data from 10 studies were included in the meta‐analysis, providing no intervention in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies reported depression as an outcome, of which seven used the Beck Depression Inventory (Bang et al, 2016, 2017; Cho et al, 2008; Chun et al, 2017; Han et al, 2016), two used Zung's Depression Scale (Choi & Ha, 2014; You et al, 2014), two used Hospital Anxiety and Depression Scale (Kim et al, 2015; Pálsdóttir et al, 2020) and one used Geriatric Depression Scale—Korea Version (Lim et al, 2014). Data from 10 studies were included in the meta‐analysis, providing no intervention in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled SMD was −0.67 (95% CI −0.99, −0.35, p < 0.001), and moderate heterogeneity was observed ( χ 2 = 29.31, p < 0.001, I 2 = 69%) (See Figure 2). Two studies (Pálsdóttir et al, 2020; Shin et al, 2012) were not included in the meta‐analysis since no standard deviations were reported, but both studies reported significantly lower scores for those in their intervention groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was conducted at Swedish University of Agricultural Sciences (SLU) Alnarp Rehabilitation Garden, a living lab, where researchers, garden members, and community partners collaborate around nature-based interventions. Several nature-based rehabilitation projects targeting diverse groups have previously been hosted by SLU Alnarp rehabilitation garden (Pálsdóttir, Stigsdotter et al, 2018;Pálsdóttir et al, 2020). The 1.5 ha SLU Alnarp Rehabilitation Garden is divided into two major areas: 1) the formal and cultivation area and 2) the informal nature area (Pálsdóttir, 2016).…”
Section: Settingmentioning
confidence: 99%